Histomorphological analysis and clinical correlation of neoplastic and non neoplastic skin lesions: a study in a tertiary care centre of Western Uttar Pradesh, India - Bisht, Mithila; Arya, Anjana; Choudhry, B. C. (International Journal of Research in Medical Sciences, 2020)
Background: Clinical examination may suffice in making diagnosis of most dermatologic disorders but histopathological examination is often required to confirm the diagnosis and further categorize the lesions. Authors carried out this study to analyse the demographic and histomorphological characteristics of skin lesions, to determine the frequency of various dermatological disorders in the region and to evaluate the agreement between clinical and histopathological diagnosis. Methods: Punch biopsies of skin lesions received in histopathology section, were included in the study. Cases over a period of six months were analysed. Clinical details were recorded and histopathological analysis done. Special stains were applied wherever required. Results: Of the 120 cases studied, maximum cases fell in the category of 31-40 years, with male predominance. Authors observed wide variety of non-neoplastic and neoplastic lesions. Infectious diseases were the most common of all pathologies. Leprosy was the most common histopathological diagnosis. Complete clinicopathologic correlation was seen in 51.67% of cases while partial correlation was noted in 23.33% making a total of 75%. 25% histopathological diagnosis were inconsistent with the clinical diagnosis. Conclusions: Histopathology is a gold standard investigation and plays a very important role in confirmation of clinical diagnosis of various skin lesions. Punch biopsy is a relatively easy outpatient procedure to perform.